LC‐ESI/HRMS analysis of glucosinolates, oxylipins and phenols in Italian rocket salad (Diplotaxis erucoides subsp. erucoides (L.) DC.) and evaluation of its healthy potential. (14th April 2021) - Loizzo, Monica R; Napolitano, Assunta; Bruno, Maurizio; Geraci, Anna; Schicchi, Rosario; Leporini, Mariarosaria; Tundis, Rosa; Piacente, Sonia
Abstract: BACKGROUND: This study investigated the chemical profile and biological activity of Diplotaxis erucoides subsp. erucoides (L.) DC. (Brassicaceae) collected in Sicily (Italy). RESULTS: Liquid chromatography coupled with electrospray ionization and high‐resolution mass spectrometry (LC‐ESI/HRMS) analysis of the ethanol extract revealed the presence of 42 compounds – glucosinolates, hydroxycinnamic acids, flavonoids, and oxylipins. The extract was tested for its antioxidant activity using 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic) acid (ABTS), ferric reducing ability power (FRAP), and β ‐carotene bleaching tests. Promising protection from lipid peroxidation was observed after 30 min of incubation in a β ‐carotene bleaching test (IC50 of 3.32 μg mL −1 ). The inhibition of carbohydrates‐hydrolyzing enzymes resulted in IC50 values of 85.18 and 92.36 μg mL −1 for α ‐amylase and α ‐glucosidase, respectively. Significant inhibition against lipase enzyme was observed (IC50 of 61.27 μg mL −1 ). CONCLUSION: Diplotaxis erucoides can be considered a potential source of antioxidant, hypoglycemic, and hypolipidemic bioactives. © 2021 Society of Chemical Industry.